Relationship between anti-Müllerian hormone concentration and antral follicle count in Colombian creole cows of the Chino Santandereano breed. - Narváez, Héctor Javier; Borda, Diego Armando Vega; Ballesteros, Esneyder Rugeles; Rey, Deicy Villalba; da Costa, Ricardo Lopes Dias (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study was to evaluate the relationship between serum anti-Müllerian hormone (AMH) concentration and antral follicle count (AFC) during the estrous cycle of Colombian Creole cows of the Chino Santandereano breed. Materials and Methods: Ten non-lactating, non-pregnant, multiparous cows of the Chino Santandereano breed (Bos taurus taurus adapted), aged between 3 and 7 years, with a body condition of 3.0 ± 0.4 and with normal reproductive tracts at the structural and functional level, were selected and used. For the synchronization of estrus and ovulation, an intravaginal progesterone release device plus 2 mg of estradiol benzoate was applied for 8 days. On day 8, 150 μg of cloprostenol sodium + 300 IU of equine chorionic gonadotropin + 1 mg of estradiol cypionate was administered. This protocol was performed to determine the antral follicular count and to quantify serum AMH levels every 5 days during the estrous cycle. Results: The mean serum AMH concentration and AFC were 725 ± 2.7 pg/ml and 43.4 ± 3.5, respectively. A high correlation was observed between AMH and AFC of r = 0.041; p < 0.0001. Conclusion: The results showed that in Creole cows of the Chino Santandereano breed, there is a high correlation between circulating levels of AMH and ovarian reserve. This mechanism can be used as an endocrine biomarker of the follicular population. J. Adv. Vet. Anim. Res., 12(2): 680–686, June 2025 http://doi.org/10.5455/javar.2025.l931